Preliminary study for the preparation of fatty acid bioconjugated L-asparaginase micellar nanocarrier as a delivery system for peptide anti-cancer agents - Hajar Ashrafi; amir Azadi; Soliman Mohammadi-Samani; Younes Ghasemi; Saeid** Daneshamouz (Shiraz University of Medical Sciences, 2020)
In the present study, the mixing behavior of different groups of surfactants and fatty acid bioconjugated L-asparaginase investigated. The amphiphilic macromolecules were achieved by covalent linkage of fatty acids with different chain lengths (C12, C16, and C22) to the native enzyme, L-asparaginase. The amino group of L-asparaginase lysine residue was conjugated to the carboxylic group of fatty acids, using a carbodiimide activator. The effect of different kinds of surfactants on particle size and enzyme activity of fatty acid bioconjugated L-ASNase was evaluated. The particle sizes of resulted micellar nanocarrier before and after lyophilization and enzyme activity investigated. Among all surfactants, pluronic F-127 with fatty acid bioconjugated L-asparaginase presented more plasma and PBS half-life. Higher activity value after lyophilization for bioconjugate with pluronic F-127 also achieved. These findings from L-asparaginase modification by fatty acid and surfactants indicate a promising stabilized product that may serve as a new candidate for medical purposes.